More fragmentized urban form more CO2 emissions? A comprehensive relationship from the combination analysis across different scales. (20th January 2020) - Zuo, Shudi; Dai, Shaoqing; Ren, Yin
Abstract: Scientifically delineating the spatial heterogeneity of urban landscape fragmentation in relation to CO2 emissions helps the urban carbon mitigation strategy. The combination analysis across spatial resolutions, which is rare, helps explore the comprehensive relationship between urban fragmentation and CO2 emissions. This study compared the relationships between urban form fragmentation and CO2 emissions in an urban system through the analytic framework composed of the Pearson correlation analysis, geographically weighted regression (GWR), and geographical detector methods with the use of multi-source data to construct the CO2 emissions maps. As the result, there was less fragmentation with a 500-m spatial resolution (R500m ) than with a 30-m spatial resolution (R30m ). In terms of the GWR analysis, the coarse resolution resulted in: 1) positive coefficients of fragmentation metric becoming negative, and 2) greater absolute values of negative coefficients. As to the results of Geographical detector, single factor impact powers and interactions among fragmentation factors showed a weakening effect at R30m, but a strengthening and weakening effect at R500m . However, there were common results observed in low-fragmented areas across different scales. That is, in low-fragmented mixed-function areas and industrial areas, the more fragmented the area was, the less the CO2 emission there would be. However, in low-fragmented residential, administrative and public service areas, the more fragmented the area was, the higher the CO2 emission there would be. Therefore, the government should disperse the mixed function zones and industrial parcels with diverse types of land, and build the contiguous residential and public service land in the low fragmentation area of urban system. The results of this study can provide a reference for the other small and medium towns and cities. The analytical framework can be applied to CO2 emissions research in urban agglomerations, megacities, and small towns. Highlights: Use of multi-source data and an analytical framework composed of 3 methods. Exploration of the impact of 30-m versus 500-m spatial resolution. Low fragmented mixed and industrial lands affect CO2 emissions negatively. Low fragmented residential and public lands affect CO2 emissions positively. Interactions of factors are weaker at a 30-m resolution than at a 500-m resolution.